The confidence interval analysis for stocks with “Unusual Market Activity” - Tarisa Syafitria Suratman; Tirsayan Ibrahim (The Contrarian : Finance, Accounting, and Business Research, 2023)
In order to protect investors, the capital market authorities actively monitor stock price movements. Unusual movements have resulted in the capital market authorities announcing unusual market activity (UMA). This study uses firms that obtain UMA status in the announcement period from March to April 2023. To analyze UMA, the study uses confidence interval estimation. The results of this study indicate that UMA status tends to be proven by paying attention to the classification of critical values ​​and the range of data